Przygotowanie kandydatów do kapłaństwa w diecezji włocławskiej w świetle potrydenckich synodów diecezjalnych - Gręźlikowski, Janusz (Prawo Kanoniczne, 2002)
Amongst many legal and disciplinary warrants and orders of Trident Council (1545-1563) which undertook energetic action to reform and revival of the church, there was a Cum adolescentium aetas decreefound, accepted on May 8th 1563, orduring to the bishops to create theological seminaries. This decree also changed the from of preparation of candidates for priesthood. Implementation into being and realization of Council’s resolutions, including the decree for theological seminaries, was depended in big extent from personal involvement of the bishops. The most effective tool for realization of Tridentinum resolutions by the bishops in individual dioceses were Diocesan Synods, pointed anyway by the Council itself as important factors of the reform. Trident reform, within the range of priests preparation for priesthood in Włocławek Diocese, found favorable conditions and resulted already in 1568 with foundation, and in 1569 with erection of diocesan seminary in Włocławek by bishop Stanislaw Karnkowski, later the primate. This seminary went through different difficulties and not always was able to fully fulfil its function. However thanks to efforts and care of Stanislaw Karnkowski’s successors, especially bishop Paweł Wolucki and Maciej Lubieński as well as the chapter, this seminary prepared candidates for priesthood according to Tridentinum spirit. Also the other seminary, called Schothand or Gdańsk seminary was to serve for that purpose, and this seminary was designated to educate candidates for holy orders inpart of Pomerania diocese, and those ones who contributes the most to this idea were bishops Hieronim Rozrażewski and Paweł Wolucki. Formation of the candidates for holy orders was outhined mainly by the following synods: Stanislaw Karnkowski’s from 1568, Wojciech Baranowski’s from 1607, Paweł Wolucki’s from 1620, Andrzej Lipski’s from 1622 and 1628 and Maciej Lubieński from 1634 and 1641. These synods, according to spirit of Trident decree, determined detailed requiremants set for aspirants for priesthood as well as they determinal wurse of the formation leading to priesthood. Big credit should be granted to initiative of bishops: Karnkowski, Baranowski and Wolucki in reference to field of awaking and shaping the priest vocation. All three men mentioned above displayed their understanding not only to dispositions and orders of Trident Council but also to real needs of the diocese. Through synod legislators who made legal regulations, the big care and concern appeared that the diocese would get well prepared and to same extent versatile formed priests for priest’s service.